Sulphide capacity prediction of CaO–SiO2–MgO–Al2O3 slag system by using regularized extreme learning machine. (16th March 2021) - Xin, Zi-Cheng; Zhang, Jiang-Shan; Lin, Wen-Hui; Zhang, Jun-Guo; Jin, Yu; Zheng, Jin; Cui, Jia-Feng; Liu, Qing
ABSTRACT: Desulphurization is essential in the steelmaking process for high-quality steel production, and sulphide capacity has proven to be an effective index to evaluate the desulphurization ability of molten slag or flux. Several analytical or empirical models have been proposed to calculate the sulphide capacity. However, these models usually show insufficient generalization ability when new variables/data are introduced, which limits their practical application. In this work, experimental data were collected from the literature and a regularized extreme learning machine (RELM) model was established to predict the sulphide capacity of the CaO–SiO2 –MgO–Al2 O3 slag system. The results demonstrated that the proposed model is robust for the prediction of sulphide capacity under different conditions. The coefficient of determination ( R 2 ), correlation coefficient (r), root-mean-square error (RMSE) of the optimal model reached 0.9763, 0.9881, 0.113, respectively, which outperform the results of the reported models.